Building public trust: Evaluating the effectiveness of digital governance and regulatory policies pawnbroking business - Sarinah (Environmental, Social, Governance and Sustainable Business, 2026)
Background: Digital transformation in Indonesia's pawnshop industry has driven significant changes in financial service patterns, ranging from accelerated transaction processes to expanded service inclusion through platforms such as Pegadaian Digital Service and Pegadaian Syariah Digital Service. However, this acceleration has also been accompanied by challenges in the form of regulatory uncertainty, increased digital risks, and variability in public trust influenced by system quality and data protection. This study aims to analyze the interaction between the digitization of pawnshop services, the dynamics of public trust, and the effectiveness of regulations by reviewing previous research developments that show a gap between technological innovation and governance readiness. Methods: This study applies a systematic literature review method with structured searches on a number of national and international academic databases, article selection using identification, screening, and eligibility stages, and thematic analysis to formulate conceptual patterns related to digital service quality, user behavior, and regulatory effectiveness. Findings: The synthesis results show that the reliability of digital systems is the strongest determinant in driving adoption and shaping user trust, while digital literacy acts as a moderating variable that explains differences in acceptance levels between demographic groups. In addition, the current regulatory framework does not adequately regulate remote appraisal practices, data security, guarantee delivery mechanisms, and digital operational standards, resulting in legal uncertainty and weak consumer protection. These findings confirm that the success of digital pawnbroking services is highly dependent on the harmonization of technology quality, user readiness, and regulatory capacity. Conclusion: This study concludes that strengthening digital governance, modernizing regulations, and improving digital literacy are key prerequisites for creating a secure, inclusive, and sustainable digital pawnbroking ecosystem. Novelty/Originality of this article: The uniqueness of this research lies in the development of an integrative conceptual model that combines digitization, public trust, and regulatory effectiveness in a holistic analytical framework, thereby enriching the literature and supporting evidence-based policy formulation in the digital pawnbroking sector.